18.4k views
4 votes
30 POINTS PLEASE HELP

30 POINTS PLEASE HELP-example-1
User Chalo
by
5.8k points

1 Answer

3 votes

Answer:

Answer:

Solution given:

f(x)=5x-3

let

y=f(x)

y=5x-3

interchanging role of x and y

x=5y-3

x+3=5y

y=
(x+3)/(5)

$o,

f-¹(x)=
(x+3)/(5)

we conclude that

f-¹(x)≠g(x)

Each pair of function are not inverses.

g(x)=x/5+3

let g(x)=y

y=x/5+3

interchanging role of x and y

x=y/5+3

x-3=y/5

doing crisscrossed multiplication

5(x-3)=y

y=5x-15

g-¹(x)=5x-15

So

g-¹(x)≠f-¹(x)

Each pair of function are not inverses.

User Mrwalker
by
5.5k points